Using a Small Lever to Achieve Big Outcomes in a Devolved Health System: 20 Years of Programa Sumar in Argentina - Martin Sabignoso; Susan P. Sparkes; Alexandra J. Earle (Taylor & Francis Group, 2024)
Incremental health system transformations towards universal health coverage run the risk of losing sight of the overarching objectives and can lose momentum in the implementation process. Argentina's Programa Sumar is a program born out of response to both urgent and long-standing health challenges. Starting with a relatively small share of the government's budget for health, the Program over the last 20 years has gradually expanded in pursuit of increasing access to quality health care, fostering coherence through policy alignment and coordination in a highly decentralized system, and achieving its performance objectives through conditional transfers linked to results. This commentary reflects on how Programa Sumar created and has sustained its approach to health system transformation and provides four lessons: 1) distribute leadership across levels of government to enhance autonomy, collaboration, and implementation; 2) expand gradually, with a clear long-term vision - Programa Sumar took an incremental approach to expansion in terms of regions, populations, services, and management capacities; 3) ensure evolution through solid and flexible design - the Program needed both the flexibility to adapt strategies to various challenges and a constancy of purpose; and 4) compromise to make progress. The Argentine experience with Programa Sumar shows that strengthening a scheme does not have to mean adopting a fragmented approach. Instead, by implementing Programa Sumar thoughtfully and collaboratively, the reform has developed a solid foundation with the flexibility to adapt across geographies and time, creating the necessary conditions for expansion to and greater coherence across the entire system.